Terminologia graeco-latina medica pro studijní obory fyzioterapie a všeobecná sestra - Švanda, Libor (Masaryk University Press, 2016)
The exercise book was written for the first-year students of physiotherapy and nursing. It introduces the basic Greek-Latin medical terminology and grammar rules, which are explained in greater detail in a separate Grammar Book. Each of the ten units consists of a set of exercises meant for both the class work and home preparation: the unit starts with a translation exercise (aimed at anatomical and later also clinical nomenclature); then, there is a series of shorter exercises for practising frequent grammatical structures and specialized vocabulary.